A Phase I, open-label, randomized, crossover study in healthy subjects to evaluate the bioavailability of, and the food effect on, a pomalidomide oral liquid suspension - Li Y (Dove Medical Press, 2018)
Yan Li,1 Liangang Liu,2 Lian Huang,3 Xiaomin Wang,4 Matthew Hoffmann,4 Josephine Reyes,1 Maria Palmisano,1 Simon Zhou1 1Translational Development and Clinical Pharmacology, 2Biometrics and Data Operations, 3Pharmaceutical Science Drug Product Development, 4Non-Clinical Development, Celgene Corporation, Summit, NJ, USA Objective: The aim of this study was to evaluate the bioavailability of a pomalidomide oral liquid suspension relative to the commercial capsule formulation and to assess the food effect on the pomalidomide oral liquid suspension when administered as a single 4 mg dose. Methods: This was an open-label, randomized, three-period, two-sequence crossover study in healthy subjects consisting of a screening phase, a baseline assessment phase, a treatment phase with three periods, and a follow-up phone call phase. Blood samples for pharmacokinetics (PK) assessment were collected up to 48 h postdose during each treatment period. Safety was evaluated throughout the study. Results: Pomalidomide exposures were comparable in healthy subjects administered with a single oral 4 mg dose as the reference capsule or as the test liquid suspension formulations, demonstrated as the 90% confidence intervals of the geometric mean ratios for area under the plasma concentration–time curve calculated from time 0 to the last measurable concentration at time t (AUC0–t), area under the plasma concentration–time curve from time 0 to infinity (AUC0–∞), and peak (maximum) plasma drug concentration (Cmax) were completely contained within the bioequivalence range of 80–125%. Administration of the pomalidomide liquid suspension with a high fat meal resulted in a 3.0 h delay in pomalidomide time to Cmax (tmax) and an ~ 34.5% reduction in Cmax. However, the AUCs were comparable after dose administration with and without food. Conclusion: A single oral dose of 4 mg of liquid suspension was bioequivalent to a single oral dose of 4 mg of capsule formulation. There was no clinically relevant impact of food on pomalidomide liquid suspension. Single oral doses of 4 mg pomalidomide were safe and well tolerated when administered as a liquid suspension under fed and fasted conditions or as a capsule under fasted conditions. Keywords: pomalidomide, liquid suspension, bioavailability, bioequivalence, food effect